Hashimoto Encephalopathy Mimicking Acute Ischemic Stroke: Perfusion-Weighted Magnetic Resonance Imaging - Cho, Bang-Hoon; Cheon, Kyeongyeol; Lee, Kyung-Yul (Journal of clinical neurology (Seoul, Korea), 2018)
KCI Citation Count: 1